Effect of grain size on structural and dielectric properties of barium titanate piezoceramics synthesized by high energy ball milling - Verma N.K.; Patel S.K.S.; Kumar D.; Singh C.B.; Singh A.K. (My University, 2025)
We have investigated the effect of sintering temperature on the densification behaviour, grain size, structural and dielectric properties of BaTiO3 ceramics, prepared by high energy ball milling method. The Powder x-ray diffraction reveals the tetragonal structure with space group P4mm for all the samples. The samples were sintered at four different temperatures, (T = 900°C, 1000°C, 1100°C, 1200°C and 1300°C). Density increased with increasing sintering temperature, reaching up to 97% at 1300°C. A grain growth was observed with increasing sintering temperature. Impedance analyses of the sintered samples at various temperatures were performed. Increase in dielectric constant and Curie temperature is observed with increasing sintering temperature. © 2018 Author(s).